PERANAN KEYAKINAN GURU TERHADAP HAKIKAT DAN BELAJAR MENGAJAR SAINS DALAM PENGEMBANGAN PROFESIONALISME - Iceng Hidayat (LPMPP Universitas Negeri Yogyakarta, 2007)
This article is a study aiming at developing a professionalismenhancingsystem that can bridge the gap between the curriculumthat prepares teachers and the teaching they practice at schools. Anunderstanding of the system of teachers' beliefs will assist inenhancing the effectiveness of the teaching of science and representsa significant indicator of teachers' behavior in the classroom. Inrelation to science, teachers believe that it is manmade so that it isimperfect and must be continuously developed. They also realizethat science is part of daily life. In teaching science, emphasis shouldbe on exploratory learning with little instruction but with a provisionof structured materials. Teachers' beliefs have important roles ininstructional reformation. Beliefs could be constructed throughactive participation and collaborative partnership so that belief andknowledge transformation can occur. Transformational andcontinuous professional development is needed to align teachers'beliefs with reformation recommendations. Successful reform inscience teaching and true implementation by the teachers as intendedwill need some kind of enabling condition. The PPGS (short forPenugasan Pendidikan Guru ke Sekolah or School AssignedTeacher Education) program is a system to accommodate thetransformational professional development of science teachers andexpected to be an agent of change in science teaching. Every reformor innovation in science teaching could be validated by being putinto practice in PPGS forums first.